Principles and methods of explainable artificial intelligence in healthcare - De Albuquerque, Victor Hugo C.; Srinivasu, Parvathaneni Naga, 1990-; Bhoi, Akash Kumar; Gonzalez Briones, Alfonso, 1985- (Advances in medical technologies and clinical practice book series., 2022)
"This book focuses on the Explainable Artificial Intelligence (XAI) for healthcare, providing a broad overview of state-of-art approaches for accurate analysis and diagnosis, and encompassing computational vision processing techniques that handle complex data like physiological information, electronic healthcare records, medical imaging data that assist in earlier prediction"--